The population status of sulphur goatfish Upeneus sulphureus in the Iraqi marine waters, northwest Arabian Gulf - Mohamed, A.R.M.; Resen, A.K. (Mesopotamian Journal of Marine Sciences, 2022)
The status of the sulphur goatfish Upeneus sulphureus Cuvier, 1829 population in the Iraqi marine waters, north-west of the Arabian Gulf was assessed using FiSAT program from March 2007 to September 2008. A total of 7574 specimens of U. sulphureus were collected by trawl net, their lengths ranged from 5 to 17cm. Length-weight relationship was W = 0.0621 L3.0125. The growth parameters estimated were L∞= 18.85cm and K= 0.72. The growth performance index (ø) of the species was computed as 2.36. Total mortality rate (Z) was computed as 2.43, natural mortality rate (M) was 1.85, fishing mortality rate (F) was 0.58 and the exploitation ratio was 0.32. The values of F and E of U. sulphureus obtained in the present study were lower than those recorded for the same species in the previous studies, whereas the population of the species exposed to higher natural mortality rate. The results indicated that the present levels of E and F were lower than those of the maximum (Y/R)'.